Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

y = x + 5 y = 2x - 7

Sagot :

y = x + 5 (eq. 1)

y = 2x - 7​ (eq. 2)

Substituting equation 1 into equation 2, we get:

x + 5 = 2x - 7

5 = 2x - 7 - x

5 = x - 7

5 + 7 = x

12 = x

Replacing this result into the first equation:

y = 12 + 5

y = 17

We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.